Cyberbullying through the lens of social influence: Predicting cyberbullying perpetration from perceived peer-norm, cyberspace regulations and ingroup processes. (January 2020) - Piccoli, Valentina; Carnaghi, Andrea; Grassi, Michele; Stragà, Marta; Bianchi, Mauro
Abstract: In the present research we analyzed the social influence mechanisms that back the relation between peer group norms regarding cyberbullying behaviors and individual cyberbullying perpetration. In a sample of adolescents (N = 3511, age: M = 16.27, SD = 1.58), we showed that the relation between perceived peer-norm and cyberbullying perpetration was moderated by two distinct social influence mechanisms. Specifically, when individuals' lack of knowledge regarding appropriate behaviors in cyberspace (i.e., cyberspace regulations), levels of perceived peer-norm regarding cyberbullying behaviors positively influence the participants' engagement in cyberbullying perpetration (i.e., informational social influence ). Moreover, we showed that the higher the support of perceived peer-norm regarding cyberbullying behaviors the higher the levels of cyberbullying perpetration, especially for the higher (vs. lower) levels of identification with peers as the ingroup; this relation was additionally enhanced at increasing levels of adolescents' ingroup prototypicality (i.e., referential informative social influence ). The results demonstrated that the two social influence mechanisms work independently and likely contribute to predict participants' engagement in cyberbullying perpetration. Results are discussed with respect to the current literature regarding the social influence mechanisms underlying cyberbullying. The implications of these findings for practical interventions are explored. Highlights: The study focuses on the relation between group-norms and cyberbullying perpetration. The lower the level of cyberspace regulations the higher the levels of cyberbullying. Ingroup identification moderates the relation between group-norms and cyberbullying. Ingroup prototypicality moderates the relation between group-norms and cyberbullying.